In-service education programs of three University of the Philippines-administered schools from 1966-1971 - Suddhapreda, Chaweewan 1940- (s.n.], 1971)
This study determined the nature of in-service education programs in the UP Elementary School, UP High School, and the UP Preparatory High School from 1966 to 1971. The normative-descriptive method was used, with documentary analysis, questionnaire, and interview as tools. It was concluded that the in-service program in the 3 UP-administered schools varied from formal to informal types. Faculty and administrators should agree on the objectives, activities, execution, and evaluation of the program.